2000
DOI: 10.1097/00005537-200011000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of the Muller Maneuver and Its Association With Sleep‐Disordered Breathing

Abstract: Objectives/Hypothesis: Use of the Muller maneuver (MM) in the evaluation of patients with obstructive sleep apnea is controversial. One criticism of this test is that it is somewhat subjective. Our objective is to explore the reliability of this technique and its association with sleep-disordered breathing. Study Design: Prospective study performed in an academic tertiary care center. Methods: An analysis of MM scores from 180 consecutive patients obtained independently by two examiners was completed. These sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
92
0
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(97 citation statements)
references
References 14 publications
1
92
0
4
Order By: Relevance
“…But only the value of pharyngeal collapse with Muller maneuver was strongly correlated with AHI (Table 4). To our knowledge, it was the most predicting factor for OSAS confirming the previous studies (5,(33)(34)(35). Nasal continuous positive airway pressure is effective in moderate to severe OSAS patients (36).…”
Section: Discussionsupporting
confidence: 86%
“…But only the value of pharyngeal collapse with Muller maneuver was strongly correlated with AHI (Table 4). To our knowledge, it was the most predicting factor for OSAS confirming the previous studies (5,(33)(34)(35). Nasal continuous positive airway pressure is effective in moderate to severe OSAS patients (36).…”
Section: Discussionsupporting
confidence: 86%
“…[17] However, the Müller maneuver may be easy to perform, provide a thorough assessment of the upper airway, enable exclusion of other lesions, and be valid when marked collapse is present (Müller grade 3 or 4). [18] In the present study, all otolaryngology examinations were performed and graded by the same otolaryngologist, and the otolaryngology evaluation was performed in consultation with a pulmonologist. More reliable associations may be observed in a study with two independent examiners (each examiner blinded to the score of the other).…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 180 patients done by Terris et al [2] checked the reliability of Muller's in OSA. The authors concluded that despite the subjective nature of the MM, the five-point scale can be used by independent examiners to achieve an evaluation of the upper airway that is reproducible.…”
Section: Discussionmentioning
confidence: 99%
“…These methods include manometry, radiographic studies including computed tomography, dynamic MRI, fluoroscopy and cephalometry and office procedure such as the Muller's maneuver (MM) [2]. MM has been used widely by clinicians during the pre operative evaluation of patients diagnosed with OSA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation